Training‐induced recovery of low‐level vision followed by mid‐level perceptual improvements in developmental object and face agnosia. Issue 1 (4th April 2014) - Lev, Maria; Gilaie‐Dotan, Sharon; Gotthilf‐Nezri, Dana; Yehezkel, Oren; Brooks, Joseph L.; Perry, Anat; Bentin, Shlomo; Bonneh, Yoram; Polat, Uri
Abstract Long‐term deprivation of normal visual inputs can cause perceptual impairments at various levels of visual function, from basic visual acuity deficits, through mid‐level deficits such as contour integration and motion coherence, to high‐level face and object agnosia. Yet it is unclear whether training during adulthood, at a post‐developmental stage of the adult visual system, can overcome such developmental impairments. Here, we visually trained LG, a developmental object and face agnosic individual. Prior to training, at the age of 20, LG's basic and mid‐level visual functions such as visual acuity, crowding effects, and contour integration were underdeveloped relative to normal adult vision, corresponding to or poorer than those of 5–6 year olds (Gilaie‐Dotan, Perry, Bonneh, Malach & Bentin, 2009). Intensive visual training, based on lateral interactions, was applied for a period of 9 months. LG's directly trained but also untrained visual functions such as visual acuity, crowding, binocular stereopsis and also mid‐level contour integration improved significantly and reached near‐age‐level performance, with long‐term (over 4 years) persistence. Moreover, mid‐level functions that were tested post‐training were found to be normal in LG. Some possible subtle improvement was observed in LG's higher‐order visual functions such as object recognition and part integration, while LG's face perception skills have not improved thus far. These results suggest that corrective training at a post‐developmental stage, even in the adult visual system, can prove effective, and its enduring effects are the basis for a revival of a developmental cascade that can lead to reduced perceptual impairments.